Ethnic differences in bone health status and its association with calcium intake, physical activity and body mass index among Malaysian older adults from Bangi and Kajang, Selangor, Malaysia - Lim, Hui Peng; Nur Syahira Nasaruddin,; Norlida Mat Daud,; Nor Aini Jamil, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The increase in sedentary activity among older adults could result in lowering bone mineral density (BMD), thus increasing the risk of osteoporosis. Physical activity and adequate dietary calcium intake (DCI) are important to optimize bone health. Therefore, this study was conducted to determine ethnic differences in bone health status (BHS) and to investigate the association between lifestyle factors and BHS among Malaysian older adults. A total of 120 older adults aged between 60 to 84 years old of three major ethnicities residing in Bangi and Kajang, Selangor, Malaysia were recruited in this cross-sectional study. They were asked to fill out food frequency questionnaire and the international physical activity questionnaires for the quantification of DCI and physical activity level (PAL) assessments. BMD was quantified using QUS-2 Calcaneal Ultrasonometer. The results showed that the Chinese participants had significantly lower body mass index (BMI) (p<0.001) than their counterparts. Malay participants had significantly higher DCI (p=0.027) compared to other groups. However, none of the participants met the recommended daily intake of calcium (1000 mg/day). The Indian participants had significantly higher (p=0.007) PAL compared to the Malay and Chinese groups. BMD analysis showed that the Chinese have significantly lower (p=0.001) T-scores (-0.54 ± 1.35) compared to Malay (0.78 ± 1.72) and Indian (0.61 ± 1.91), respectively. BMI and DCI were positively correlated with BMD (correlation coefficient, r= 0.320, p<0.001; r=0.383, p<0.001, respectively). In conclusion, the reduced BMI among the Chinese and DCI among all Malaysian older adults need to be concerned and addressed immediately. Future intervention programs should be focusing on optimizing DCI, not only among the older adults but should be emphasized and initiated at younger ages to prevent osteoporosis during old age.